Economic Impact of Proposal to Raise Cigarette Prices in Military Commissaries (Tufts Archival Research Center, 2007)
Missing Page(s); Executive summary and introduction to a report on the economic impact of raising the price of cigarettes in military commissaries. Discusses differential impacts of proposed policy. Finds that military personnel do not smoke more than the average person. Concludes that ammendment is inequitable and would have negligible benefits.